2022
DOI: 10.3390/ijms231911835
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine, Schizophrenia and Cancer: Does the Purinergic System Offer a Pathway to Treatment?

Abstract: For over a century, a complex relationship between schizophrenia diagnosis and development of many cancers has been observed. Findings from epidemiological studies are mixed, with reports of increased, reduced, or no difference in cancer incidence in schizophrenia patients. However, as risk factors for cancer, including elevated smoking rates and substance abuse, are commonly associated with this patient population, it is surprising that cancer incidence is not higher. Various factors may account for the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 203 publications
0
3
0
Order By: Relevance
“…Schizophrenia is a serious mental illness that affects the thinking, behavior, and emotions of patients (1). Recent studies have demonstrated a complex relationship between schizophrenia and tumor incidence (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schizophrenia is a serious mental illness that affects the thinking, behavior, and emotions of patients (1). Recent studies have demonstrated a complex relationship between schizophrenia and tumor incidence (2).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding this relationship may help us better understand the pathological mechanisms of schizophrenia and provide new implications for future treatment strategies. The relationship between schizophrenia and tumors is complex and delicate (2). Further research is needed to explore and understand this relationship to provide a scientific basis for the prevention and treatment of schizophrenia and tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The review by Hamoud et al [7] explores the potential relationship between adenosine, schizophrenia, and cancer. They detail the incidence of cancer in schizophrenia, extracellular adenosine metabolism, adenosine receptor signaling and uric acid metabolism, before outlining the evidence for adenosine system perturbations in schizophrenia, and the role of extracellular adenosine generation in cancer and its potential as a therapeutic target in this disease.…”
mentioning
confidence: 99%